Beech leaf disease: An emerging forest epidemic. Issue 2 (25th December 2018) - Ewing, Carrie J.; Hausman, Constance E.; Pogacnik, John; Slot, Jason; Bonello, Pierluigi
Abstract: Beech leaf disease (BLD) is a currently undiagnosed and seemingly lethal disease that was discovered in 2012 on American beech trees ( Fagus grandifolia ) in north‐east Ohio in the United States. Since its discovery, BLD has spread rapidly and can now be found in forests in 10 counties in Ohio, eight counties in Pennsylvania and five counties in Ontario, Canada. The initial symptoms of the disease appear as a dark green, interveinal banding pattern on the lower canopy foliage. These initial symptoms typically occur in the shrub or sampling layer of a beech stand. The later symptoms result in solidly darkened leaves that are shrunken and crinkled. The symptoms appear to progress through the buds as the affected buds are eventually aborted and no new leaves are produced. We fear this disease has the potential to drastically alter the Eastern deciduous forests of the United States on its own and through potential compounding disease effects. In addition, BLD poses a threat to global forests as symptoms of the disease were detected on European ( F. sylvatica ) and Oriental ( F. orientalis ) beech species in nurseries in north‐eastern Ohio. Due to its rapid spread and variability in environmental conditions where it has been detected, it seems unlikely that BLD is an abiotic disorder. Thus, intense efforts are underway to determine the causal agent of BLD. Relevant stakeholders are advised to be alert for BLD symptoms in beech forests in the Northern Hemisphere, and substantial resources should be invested in understanding this emerging forest disease.